2015
DOI: 10.1002/jssc.201500705
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of six iridoid glycosides fromgardenia jasminoidesfruit by medium-pressure liquid chromatography combined with macroporous resin chromatography

Abstract: Gardeniae fructus is one of the most frequently used herbs in traditional Chinese medicine. In the present study, a process for the enrichment of six iridoid glycosides from Gardeniae fructus was developed using medium-pressure liquid chromatography combined with macroporous resin and reversed-phase chromatography. The purities of different fractions from Gardeniae fructus were assessed using quantitative high-performance liquid chromatography. After fractionation using HPD-100 column chromatography, a 30% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In the last few years, macroporous adsorption resins, one kind of promising adsorption material with many advantages, such as low cost, high adsorption capacity, and effortless regeneration, have been widely used for the enrichment of various active ingredients . However, there are also some problems in the application of macroporous resins.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, macroporous adsorption resins, one kind of promising adsorption material with many advantages, such as low cost, high adsorption capacity, and effortless regeneration, have been widely used for the enrichment of various active ingredients . However, there are also some problems in the application of macroporous resins.…”
Section: Introductionmentioning
confidence: 99%
“…Then, these six iridoid glycosides constitute the characteristic high-content chemical constituent group of Fructus Gardeniae from Jiangxi province. Iridoid glycosides have been demonstrated to be the major bioactive ingredients in Fructus Gardeniae [ 28 30 ], among which, geniposide is the quality control standard recorded in the Chinese Pharmacopoeia (2000–2015 edition) [ 31 ], and gardenoside as a hydroxylation product of geniposide is also an important constituent in Fructus Gardeniae [ 5 , 6 ]. This is similar to those recorded in ancient Chinese materia medica books.…”
Section: Discussionmentioning
confidence: 99%
“…Fructus Gardeniae has been reported to protect the liver and gallbladder cells from infringement, treat cardiovascular and cerebrovascular diseases, and promote ligament cell proliferation and collagen synthesis effectively [ 5 , 6 ]. Researchers found that the chemical composition of Fructus Gardeniae includes iridoid glycosides [ 5 , 7 ], crocins [ 8 ], phenylpropanoids [ 9 ], glycoprotein [ 10 ], and polysaccharides. Among those, iridoid glycosides are the major active constituents in Fructus Gardeniae [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medium‐pressure liquid chromatography (MPLC) is a modern technology that could provide high efficiency and recovery. Besides, MPLC has advantages of high sample loading, high throughput, short separation time, and ease of operation . In the present study, MPLC is selected for enrichment of the minor flavonoids from barley seedlings.…”
Section: Introductionmentioning
confidence: 99%